Vloga Inštituta za kovinske materiale in tehnologije pri remontnih delih v JE Krško - Vojvodič-Tuma, Jelena (Kovine zlitine tehnologije, 1995)
Institute of metals and technology is an authorised supervising organisation for construction, test operation, start, and operation of nuclear power plant. We present Institute activities needed for releasing expertise on repeated start of reactor after outage 1995 and fuel replacement in Nuclear power plant Krško. Non - destructive methods applied on steam generators and reactor vessel head penetrations are explained, as well as an example of determination of erosion/corrosion and acceptance criteria.
Keywords: Nuklearna elektrarna Krško; uparjalniki; reaktorska posoda